2013
DOI: 10.1080/00207543.2013.831190
|View full text |Cite
|
Sign up to set email alerts
|

Pressure analysis for green supply chain management implementation in Indian industries using analytic hierarchy process

Abstract: Due to growing awareness about environment protection, firms are forced to implement environmental practices to enhance their green image. In recent times, academicians and practitioners have shown interest in green marketing and green supply chain management (GSCM). Fields of green branding and sustainability have seen special interest from different business disciplines including information management, marketing, supply chain management, etc. Due to economical and ecological impact, there is a growing conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(115 citation statements)
references
References 66 publications
3
110
0
2
Order By: Relevance
“…Henceforth, it distinguishes the course of the relationship of the variables yet at the same time neglects to perceive their weightage. Other MCDM tools like ELECTRE and TOPSIS has restricted acknowledgement among practitioners and researchers (Mathiyazhagan et al, 2013;Kumar et al, 2015aKumar et al, , 2015bKumar et al, , 2015cKumar et al, , 2015d. Another MCDM tool is ANP which requires a few comparison pair-wise matrices that add complexity to the study for expert members (Harputlugil et al, 2011) as compared with AHP (Mathiyazhagan et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Henceforth, it distinguishes the course of the relationship of the variables yet at the same time neglects to perceive their weightage. Other MCDM tools like ELECTRE and TOPSIS has restricted acknowledgement among practitioners and researchers (Mathiyazhagan et al, 2013;Kumar et al, 2015aKumar et al, , 2015bKumar et al, , 2015cKumar et al, , 2015d. Another MCDM tool is ANP which requires a few comparison pair-wise matrices that add complexity to the study for expert members (Harputlugil et al, 2011) as compared with AHP (Mathiyazhagan et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, AHP is useful when a large number of factors are employed [11]. Some studies, for instance [12][13][14][15][16][17][18], articulate the advantages of AHP within their research; Liberatore and Nydick [19] argue that AHP allows decision makers to ensure the consistency of their judgments towards factors. Many recent studies successfully apply AHP in manufacturing sectors.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Green logistics practices could efficiently decrease the negative environmental impact and maintain or improve cost reduction, energy conservation, and competitiveness [15,20,21]. Moreover, many researchers found that environmental regulation issued by the government is a critical factor in promoting the green logistics practices of different sectors [15,[22][23][24]. Hence, stricter regulations are formulated to promote green logistics practices, decrease GHG emissions, and minimize the damage to the environment throughout the globe, such as the United States' implementation of the Transportation Equity Act for the 21st Century in 1998 to reduce the environmental pollution, promote employment, and construct a safe transportation system.…”
mentioning
confidence: 99%